Bio-based materials in tribology: New salicylate ionic liquid+ZnO nanolubricant of PLA and PLA nanocomposite - Sánchez-Rodríguez, C.; Pamies, R.; Sanes, J.; Carrión-Vilches, F.J.; Bermúdez, M.D. (Tribology international, 2024)
ZnO nanoparticles have been dispersed (in 0.05; 0.5 and 1.0 wt% proportions) in the protic ionic liquid bis(2-hydroxyethyl) ammonium salicylate (DSa) to obtain new (DSa+ZnO) nanofluids. A non-Newtonian behavior was found for ZnO concentrations lower than 1 wt%. The Newtonian DSa+ 1 wt%ZnO nanofluid was selected as lubricant of polylactic acid (PLA) and as 5 wt% additive to obtain the new PLA+ (DSa+ZnO) nanocomposite. PLA+ZnO was also studied as a reference. The excellent friction-reducing and antiwear behavior of PLA+ (DSa+ZnO) is attributed to the porosity that promotes self-lubrication and to synergy due to interactions between the salicylate anion in DSa and the surface of ZnO nanoparticles. Electron microscopy (SEM and TEM), Raman spectroscopy, thermal analysis (DSC and TGA) and profilometry techniques were used. [Display omitted] •New ionic liquid-ZnO nanolubricants show non-Newtonian behavior for ZnO lower than 1 wt%.•The Newtonian ionic liquid+1 wt.% ZnO nanolubricant was selected as PLA filler.•PLA modified by ionic liquid or ionic liquid+ZnO show a self-lubricating behavior.•Both DSa and ZnO fillers prevent wear of PLA matrix.•The best performance is obtained for the combined action of both additives.